Unidade Didática com Gênero Discursivo Memes: uma proposta dialógica de desenvolvimento da leitura com séries finais do ensino fundamental - Varnier, Henry Marcelo (2021)
In recent times, it is possible to observe a change related to the activity of Reading in Portuguese Language classes, regarding student interests: commonly addressed texts in the classroom, such as literary, journalistic and argumentative texts were replaced in teenagers' taste for hybrid multisemiotic discursive genres, common in social networks. The meme is one of the appreciated and shared genres by students in their daily lives. Given the marked exposure to texts of this genre, we defined that the central objective of our research would be to reflect on the potential that creation of a Didactic Unit can offer for the expansion of a careful and attentive reading of students of the 8th grade of elementary school (EF), from the work with activities that explore texts/utterances of meme discursive genre. This work presents the following question: how to develop a planned Didactic Unit with the meme discursive genre in order to encourage a careful and attentive reading of elementary school students? Dialogism studies, which are discourses generated from other discourses that already exist in the dialogic relationships of individuals and discourse genres, relatively stable types of utterances used with a certain standardization by them, support our research and were carried out by Bakhtin (2003) and Bakhtin/Volochinov (2004). These studies are expanded, in this research, by explainers, such as Brait (2012, 2013), on the Theory of Dialogic Discourse Analysis (ADD) and verb-visuality; Dionisio (2007), Rojo (2012) and Ferreiro (2013) on multimodality and Soares (1998), Rojo (2009) and Rojo and Moura (2012) on multiliteracies. For the elaboration and reflection of the meme interpretation activities in Didactic Unit, we used adapted questionnaire models from Costa-Hübes (2017) on the extraverbal and verbal-visual dimensions of the discursive genres. Methodologically, it is a qualitative research, since it combines research with classroom practice, as well as interpretive, since we aimed to reflect on the issue of reading and to seek strategies to increase the levels of criticality in students. The characterization of the meme genre, as well as the presentation of several utterances related to that, in addition to the elaboration of the Didatic Unit (UD) activities are also objectives of this work. We didn‟t intend to apply UD due to the limitations imposed by the Covid-19 pandemic. However, we presented conceptual reflections on the subject, highlighting possibilities for activities that can provide development and expansion of criticality on final grades of elementary school students.